Basketball in the Northland: a community account of the political economy and racial dynamics of youth basketball in a “hockey town” - Torkelson, Jason; Robinson, Tyrell (Frontiers in Sports and Active Living, 2023)
This article utilizes twenty-seven in-depth interviews to explore the socio-cultural position, surrounding racial politics and local economy of youth basketball in the somewhat novel setting of Northland—a mid-sized Midwestern city where hockey dominates the sporting landscape, indoor basketball facilities are relatively sparse, and outdoor play is hampered by snow coverage that frequently lasts more than half the calendar year. Narratives are primarily gathered from basketball community members (e.g. organizers, coaches, former players) and connect with city histories of redlining, school redistricting, and regional deindustrialization in ways that inform present-day constructions of playing style, stereotyping, race, and rivalry, as well as the current horizons of opportunity and access for Northland youth. Our ground-up community-focused data foreground efforts and hurdles to providing effective mentorship and actualizing basketball’s ethos of community wellness in this fold as this transpires against the increasingly higher stakes contours of youth sports broadly, which informs pertinent issues pertaining to player development, but contrasts the common tendency toward engaging these from elite levels downward, or within newer cultures of upper/middle class parenting. Ultimately, the descriptively rich ways and frequent starkness with which potential challenges regarding player interest, coaching, funding and access—both in and out of the recent covid restrictions—come to bear through our grassroots approach at the unique intersections of Northland’s weather, sports, and racial-political climates may prove clarifying for connecting with similar issues elsewhere.